2022
DOI: 10.1111/faf.12662
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable development outcomes of livelihood diversification in small‐scale fisheries

Abstract: In low-to middle-income countries, rural people often employ a diverse portfolio of livelihood activities across multiple sectors in a complex and dynamic way (Barrett et al., 2001;Scoones, 2009).Rural livelihoods scholarship commonly finds that people with diverse livelihood activities are less vulnerable or more resilient than those with a greater reliance on fewer sources of food and income

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…This study reiterates other recent findings (e.g. Eriksson et al 2020 ; Roscher et al 2022a ) in showing that assumptions surrounding rural coastal livelihoods should be tested, as realities may differ. In this context of Zanzibar’s MPAs, it was found that livelihoods are highly dynamic and for women there has been an almost entire shift away, within 6 years, from seaweed farming into small-scale business and fisheries.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study reiterates other recent findings (e.g. Eriksson et al 2020 ; Roscher et al 2022a ) in showing that assumptions surrounding rural coastal livelihoods should be tested, as realities may differ. In this context of Zanzibar’s MPAs, it was found that livelihoods are highly dynamic and for women there has been an almost entire shift away, within 6 years, from seaweed farming into small-scale business and fisheries.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, interventions may generate community support for MPAs through buy-in mechanisms which can help build trust and compliance (Tobey and Torell 2006 ). The materialisation of positive outcomes from these livelihood interventions, which can be exogenous (externally induced) or endogenous (self-induced), is often assumed, yet when empirically tested, outcomes can be highly mixed (Roscher et al 2022a ). Importantly, introducing diversified and alternative sources of income does not necessarily translate to exits from resource extractive activities, such as fishing (de la Torre-Castro and Lindström 2010 ; Cinner 2014 ; Katikiro 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas most asset‐rich households relied less on fishing for income, quantities harvested were much larger than “high reliance‐low harvest” poor households. This finding highlights the importance of understanding the role of fisheries for asset‐rich households with high harvests and low fishing reliance, and crucially, to find strategies that avoid or limit the use of alternative sources of income to subsidize increases in fishing efforts (Roscher et al, 2022). Further, asset‐rich households who specialize in fishing because of higher returns afforded by more capital‐intensive operations may be more likely to resist initiatives to collectively manage local fisheries and to invest beyond the fishery sector (Coomes et al, 2004; Poissant, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Recommendations to improve fisher household resilience when confronted by disruptions include 'diversifying livelihood(s) to reduce dependency on the fishery and provide for additional sources of income and food' (Ferrer et al, 2021: 99). Diversification of income sources for small scale fisherfolk is a common practice by both men and women as a potential way out of poverty (de Steenhuijsen Piters et al, 2021;Roscher et al, 2022). However, we focus specifically on diversification by women in fisheries due to the extent to which they dominate diversification in fishing businesses (see: Gopal et al, 2020;Gustavsson, 2020).…”
Section: The Burden Of Diversificationmentioning
confidence: 99%